¿Qué hacer con textos que no se pueden publicar? Datos derivados, criterios FAIR y TEI - José Calvo Tello; Nanette Rißler-Pipka (Journal of the Text Encoding Initiative)
In certain circumstances, data prepared by projects cannot be published openly. In the last decades different projects have published derived data (also called extracted features) to avoid this problem. In this article, we argue in favor of TEI as a format for this task, as it favors compliance with the FAIR principles. Furthermore, we present different options, discuss their advantages and disadvantages and show concrete applications to several projects with Spanish texts (CORDE, novels of the Silver Age and texts by Picasso).